A review of the incidence of tumor lysis syndrome in patients with chronic lymphocytic leukemia treated with venetoclax and debulking strategies. Issue 2 (5th April 2022) - Sharman, Jeffrey P.; Biondo, Juliana M. L.; Boyer, Michelle; Fischer, Kirsten; Hallek, Michael; Jiang, Dingfeng; Kater, Arnon P.; Porro Lurà, Michele; Wierda, William G.
Abstract: We reviewed the literature (January 2010–June 2021) on the effectiveness of debulking strategies before venetoclax initiation in patients with chronic lymphocytic leukemia to reduce tumor burden, downgrade tumor lysis syndrome (TLS) risk, and avoid hospitalization. Low TLS incidence and reduced TLS risk based on tumor burden were reported following debulking in clinical trials. Real‐world observational studies reporting debulking regimens recorded no TLS events, and those without debulking strategies had greater TLS incidence. Debulking prior to venetoclax considerably reduces TLS incidence. Further clinical trials and real‐world studies may provide additional evidence on effectiveness of debulking in reducing TLS incidence and hospitalization need.